How positional constraints affect footedness in football: A notational analysis of five leagues in Europe - Marcori, A. J.; Giovanini, B.; Martins Monteiro, P. H.; Bertoli Nascimento,V.; Brito de Souza, D.; Alves Okazaki, V. H. (Journal of Motor Behavior, 2022)
In elite-level soccer, the ability to take shots with both limbs from different positions in the pitch may be key to success. This research aimed to: 1) analyze footedness of elite-football players in European leagues during shooting by computing frequency of right- and left-foot use and accuracy; and 2) investigate whether an athlete`s distance from the target (goal, penalty, and outside penalty area) and pitch zone (center, left, or right from the goal) can constrain foot selection during shooting. We analyzed 1826 games from the 2017/18 season, divided between: Spanish LaLiga (380 matches); Italian Serie A (380 matches); English Premier League (380 matches); German Bundesliga (306 matches); and French Ligue 1 (380 matches). Results revealed asymmetrical proportions of foot selection, favoring the preferred foot for right- and left-footed athletes. Frequency of preferred foot selection increased as a function of distance from the target (i.e., the farther the athlete, higher the percentage of preferred foot selection). Shots taken from the left side were more often performed with the right foot and vice-versa, for both left- and right-footed athletes. Interestingly, asymmetries were observed only in foot selection, but not in performance, as success rate did not vary between limbs in any position.